Intravital imaging of host-parasite interactions in skin and adipose tissues - Niz, Mariana De; Frischknecht, Friedrich (Cellular microbiology, 2019)
Intravital microscopy allows the visualisation of how pathogens interact with host cells and tissues in living animals in real time. This method has enabled key advances in our understanding of host-parasite interactions under physiological conditions. A combination of genetics, microscopy techniques, and image analysis have recently facilitated the understanding of biological phenomena in living animals at cellular and subcellular resolution. In this review, we summarise findings achieved by intravital microscopy of the skin and adipose tissues upon infection with various parasites, and we present a view into possible future applications of this method.
Gesehen am 15.05.2019